ROS-Nrf2 pathway mediates the development of TGF-β1-induced epithelial-mesenchymal transition through the activation of Notch signaling - Kai Yazaki (Elsevier, 2021)
Epithelial-mesenchymal transition (EMT) is a cellular process by which epithelial cells transform to acquire mesenchymal phenotypes. Accumulating evidence indicate the involvement of EMT in the progression of malignant diseases. Notch signaling mediates TGF-β1-induced EMT through direct transcriptional activation of Snai1. The molecular mechanism how TGF-β1 activates Notch signaling, however, remains unknown. In this study, we show a pivotal role for reactive oxygen species (ROS)-Nrf2 pathway in TGF-β1-induced Notch signaling activation and EMT development. TGF-β1 induces Nrf2 activation through ROS production. Inhibiting Nrf2 activation either by reducing ROS levels by N-acetylcysteine or by knocking down of Nrf2 by small interfering RNA attenuated both Notch signaling activation and EMT development. TGF-β1 induced the transcription of Notch4 via Nrf2-dependent promoter activation. In conclusion, our study indicates the ROS-Nrf2 pathway mediates the development of TGF-β1-induced EMT through the activation of Notch signaling.